2012
DOI: 10.1074/jbc.m112.359737
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus CymR Is a New Thiol-based Oxidation-sensing Regulator of Stress Resistance and Oxidative Response

Abstract: Background:The master regulator of cysteine metabolism-CymR influences S. aureus stress resistance and virulence. Results: Mutation of the sole cysteine residue Cys-25 to Ser eradicates the redox sensing ability of the protein. Conclusion:CymR is a new thiol-based oxidation-sensing regulator. Significance: Elucidating the oxidation-sensing mechanism of CymR is important for understanding oxidation sensing by S. aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…In fact, we found that Cys-phosphorylation also occurs to other global transcriptional regulators such as CymR (at the sole Cys-25 residue) (Fig. S12), a recently identified oxidation-sensing protein responsible for cysteine metabolism regulation in S. aureus (60). Given that all of the proteins we have shown to undergo Cys-phosphorylation are global regulators that control a broad spectrum of genes and properties in S. aureus, this study may suggest a previously unexplored paradigm of Cys-phosphorylation playing important roles in biological regulation in various organisms.…”
Section: Discussionmentioning
confidence: 83%
“…In fact, we found that Cys-phosphorylation also occurs to other global transcriptional regulators such as CymR (at the sole Cys-25 residue) (Fig. S12), a recently identified oxidation-sensing protein responsible for cysteine metabolism regulation in S. aureus (60). Given that all of the proteins we have shown to undergo Cys-phosphorylation are global regulators that control a broad spectrum of genes and properties in S. aureus, this study may suggest a previously unexplored paradigm of Cys-phosphorylation playing important roles in biological regulation in various organisms.…”
Section: Discussionmentioning
confidence: 83%
“…The success of the bacterium in pathogenesis is mainly attributed to its sophisticated signaling and response systems, including global transcriptional regulators, and various two-component systems, which the bacterium uses to sense a variety of signals and environmental stimuli (28)(29)(30)(31)(32)(33)(34). Despite the recognized importance of quinone in cellular processes, its role in bacterial gene regulation and signal transductions in human pathogens remains elusive.…”
Section: Molecular Mechanism Of Quinone Signaling Mediated Through S-mentioning
confidence: 99%
“…Strikingly, cysteine phosphoylation and associated regulatory effects can be readily reversed under reducing conditions. In this same report CymR, an additional SarA/MgrA family member from S. aureus that regulates cysteine metabolism in response to oxygen, 89 was also found to be phospho-regulated by Stk1 through a similar N-terminal cysteine residue. 88 A collective model for virulence factor regulatory control is thus proposed, whereby cysteine oxidation and phosphorylation act together to control dissociation of SarA/ MgrA regulators from target promoters, which results in the activation of virulence factors (e.g., hemolysin 88 ) (Figs.…”
Section: Staphylococcus Aureusmentioning
confidence: 78%